Sex and gender medicine in physician clinical training: results of a large, single-center survey. Issue 1 (October 2016) - Dhawan, Shivani; Bakir, May; Jones, Erika; Kilpatrick, Sarah; Merz, C.
Abstract Background "Sex and Gender Medicine" is a novel medical discipline that takes into account the effects of sex and gender on the health of women and men. The Institute of Medicine in the USA declared in its 2001 and 2010 statements that being a woman or a man significantly impacts the course of diseases, and therefore, this fact must be considered in diagnosis and therapy. We evaluated the representation of Sex and Gender Medicine in clinical training at Cedars-Sinai Medical Center, a large, tertiary, non-profit, academic medical training center in the Western United States. Methods Post-graduate physician trainees (residents and fellows) in all medical and surgical departments (medicine, surgery, OB-GYN, pediatrics, anesthesiology, pathology, urology, electrophysiology, pulmonary critical care, cardiology, women's heart, medical genetics, radiology, neurosurgery, and radiation oncology) were surveyed online; 80 (55 and 45 % female and male residents, respectively) out of 890 physicians (9 % response rate) responded to questions regarding sex and gender-based medicine. Results Seventy percent of post-graduate physician trainees indicated that gender medicine concepts are never or only sometimes discussed/presented in their training program. Slightly greater than 70 % of the trainees indicated that gender concepts are never or only sometimes incorporated into didactic lectures or clinical teaching. However, more than 65 % felt that gender medicine concepts are important, and 60 % agreed that gender medicine curriculum should be implemented and taught in their clinical program. Conclusions Current physician trainees endorse both a current lack of and need for Sex and Gender Medicine clinical training.